2021
DOI: 10.1371/journal.pone.0253658
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Mycobacterium tuberculosis cell-free DNA for tuberculosis: A systematic review and meta-analysis

Abstract: Background Diagnosis of tuberculosis (TB) is still difficult. The purpose of our study was to evaluate the diagnostic accuracy of Mycobacterium tuberculosis cell-free DNA (cfDNA) for diagnosing of TB. Methods We searched relevant databases for studies that used cfDNA to diagnose TB. We evaluated the accuracy of cfDNA compared with the composite reference standard (CRS) and culture. True positive, false positive, false negative, and true negative values for cfDNA were obtained first, then the estimated pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…CRISPR-TB detected Mtb -cfDNA (median 0·13 copies per μL, IQR 0·07–1·57; mean 5·58 copies per μL, SD 18·25) in the earliest available serum of 102 children ( figure 3A ; appendix p 11), and about half had Mtb -cfDNA concentrations lower than the LOD of PCR (0·25 copies per μL; appendix p 10) in agreement with previously reported PCR analytical 22 and diagnostic sensitivity estimates. 9 11 Median CRISPR-TB signal of children with confirmed and unconfirmed tuberculosis was significantly higher than among children with unlikely tuberculosis who met no NIH tuberculosis criteria. Median CRISPR-TB among children with unlikely tuberculosis with any NIH tuberculosis criterion was higher than those with no NIH criteria, but not significantly so ( figure 3C ; table 2 ; appendix p 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CRISPR-TB detected Mtb -cfDNA (median 0·13 copies per μL, IQR 0·07–1·57; mean 5·58 copies per μL, SD 18·25) in the earliest available serum of 102 children ( figure 3A ; appendix p 11), and about half had Mtb -cfDNA concentrations lower than the LOD of PCR (0·25 copies per μL; appendix p 10) in agreement with previously reported PCR analytical 22 and diagnostic sensitivity estimates. 9 11 Median CRISPR-TB signal of children with confirmed and unconfirmed tuberculosis was significantly higher than among children with unlikely tuberculosis who met no NIH tuberculosis criteria. Median CRISPR-TB among children with unlikely tuberculosis with any NIH tuberculosis criterion was higher than those with no NIH criteria, but not significantly so ( figure 3C ; table 2 ; appendix p 12).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive detection of circulating Mtb -cfDNA could potentially identify both pulmonary tuberculosis and extrapulmonary tuberculosis given that Mtb -cfDNA released during apoptosis and M tuberculosis lysis 9 , 23 should accumulate in the circulation during tissue perfusion irrespective of its sites of origin. However, previous studies have determined that Mtb -cfDNA circulates at very low concentrations, 22 resulting in poor and highly variable diagnostic sensitivity, 9 11 which was not improved by use of a CRISPR assay with a high LOD. 14 Here we provide evidence that the combination of an assay optimised for serum cfDNA extraction and sensitive and specific target amplification and cleavage can sensitively detect serum Mtb -cfDNA in most patients with tuberculosis, including those missed by sputum-based diagnostics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While there are no validated blood tests for active TB, there is increasing optimism regarding the detection of antigens, immune cell profiling, host transcriptomics, or cell-free Mtb DNA. 62 Several studies have demonstrated associations between host mRNA signatures and TB risk, although preventive therapy guided by one such mRNA biosignature failed to reduce TB incidence in a large randomised controlled trial. 63 Despite commercial progress to develop mRNA biosignature assays, foremost of which is the Xpert Host Response (Xpert HR) cartridge that detects a 3-gene signature in capillary blood directly using the widely-deployed GeneXpert platform, 64 independent validations 65 , 66 demonstrate most transcriptomic biomarkers will not meet the WHO diagnostic accuracy criteria for triage or confirmation.…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…Proof-of-concept data has been generated for Mtb DNA detection in peripheral blood mononuclear cells 80 and cell-free DNA but no prototypes with public data are available. 62 , 81 …”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%